Let's simplify the given expression step by step and then determine which of the options are equivalent to it.
The expression given is:
\[ (3x - 8) + (2x + 5) - (4x - 8) \]
First, simplify the expression:
- Remove the parentheses:
\[ 3x - 8 + 2x + 5 - 4x + 8 \]
- Combine like terms:
- For the \(x\) terms: \(3x + 2x - 4x = (3 + 2 - 4)x = 1x = x\)
- For the constant terms: \(-8 + 5 + 8 = (-8 + 8) + 5 = 0 + 5 = 5\)
So the simplified expression is:
\[ x + 5 \]
Now, let's evaluate each of the responses to see which ones are equivalent to \(x + 5\):
-
\(3x−8+2x+5−4x−8\):
- Simplifies to \(x + 5\) (equivalent).
-
\(3x−8+2x+5−4x+8\):
- Simplifies to \(x - 8 + 5 + 8 = x + 5\) (equivalent).
-
\(3x + 2x - 4x - 8 + 5 + 8\):
- Simplifies to \(x - 8 + 5 + 8 = x + 5\) (equivalent).
-
\(5x−4x−8+5+8\):
- Simplifies to \(x - 8 + 5 + 8 = x + 5\) (equivalent).
-
\(x−8+5+8\):
- Simplifies to \(x - 8 + 5 + 8 = x + 5\) (equivalent).
-
\(x−13+8\):
- Simplifies to \(x - 5\) (not equivalent).
-
\(x−3+8\):
- Simplifies to \(x + 5\) (equivalent).
-
\(x−21\):
- Simplifies to \(x - 21\) (not equivalent).
-
\(x+5\):
- This is directly \(x + 5\) (equivalent).
So, the expressions that are equivalent to \(x + 5\) are:
- \(3x−8+2x+5−4x−8\)
- \(3x−8+2x+5−4x+8\)
- \(3x + 2x - 4x - 8 + 5 + 8\)
- \(5x−4x−8+5+8\)
- \(x−8+5+8\)
- \(x−3+8\)
- \(x+5\)
These are the equivalent expressions.